FASTING IN FIQH: COMPLETE UNDERSTANDING FOR CLASS 7 AND PREPARATION TO WELCOME RAMADHAN - Sendy Ainun Nadjib; Suhartono Hafid Musthofa; M. Mahbubi (International Journal of Multidisciplinary Reseach, 2025)
This study aims to analyze the understanding of grade 7 students at MTS Ihya Ulumiddin Tangerang about the material of fasting fiqh and their preparation in welcoming the month of Ramadan. The approach used in this study is descriptive qualitative, with data collection through observation, interviews, and documentation. The results of the study indicate that although students understand fasting as an obligation that must be carried out, their understanding is limited to technical aspects, such as the time for sahur, breaking the fast, and things that break the fast. The spiritual and moral dimensions of fasting, such as controlling lust, increasing patience, and improving morals, are still not understood. Students' preparation for welcoming the month of Ramadan also seems less than optimal, focusing more on physical and technical aspects than spiritual readiness. Learning fasting fiqh at MTS Ihya Ulumiddin Tangerang still uses methods that tend to be conventional, with little attention to the spiritual dimension of fasting. Based on these findings, it is recommended that the teaching method of fasting fiqh be updated with a more holistic approach, integrating technical and spiritual aspects, and involving students in practical and social activities that can strengthen their understanding of the wisdom of fasting and preparation for welcoming Ramadan.